Match-play load in roller hockey - Blanco, A.; Ensenyat, A. (International Journal of Computer Science in Sport, 2002)
Roller hockey is a team sport, where two teams each with four players and a goalkeeper compete for 50 min on a 40 x 20 m court, trying to introduce the ball into the opposing team`s goal. In this study, an exhibition match-play between two professional roller hockey teams was analysed with the purpose to examine the load profile and to investigate the relationship between load levels and the changes of cortisol and creatin kinase (CPK) blood levels.